Rethinking the secular origins of the novel: the Bible in English fiction 1678-1767 - Seidel, Kevin (Cambridge University Press, 2021)
"Literary histories of the novel tend to assume that religion naturally gives way to secularism, with the novel usurping the Bible after the Enlightenment. This book challenges that teleological conception of literary history by focusing on scenes in seventeenth- and eighteenth-century fiction where the Bible appears as a physical object. Situating those scenes in wider circuits of biblical criticism, Bible printing, and devotional reading, Seidel cogently demonstrates that such scenes reveal a great deal about the artistic ambitions of the novels themselves and point to the different ways those novels reconfigured their readers' relationships to the secular world. With insightful readings of the appearance of the Bible as a physical object in fiction by John Bunyan, Daniel Defoe, Samuel Richardson, Sarah Scott, Frances Sheridan, and Laurence Sterne, this book contends that the English novel rises with the English Bible, not after it"--